Entity of Behavioral Arts Performing Music Tradition Jaranan Pogogan During Pandemic - Yunanto Tri Laksono (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2021)
Changes in art and culture require a period of interrelated change withthe existence of a virtual-based creative industry during the pandemic.These changes occur because of the community's efforts to adapt tonew needs, conditions, and conditions that arise in line with thegrowth of society. The government's policy is to carry out all activitiesat home, in order to cut the chain of the spread of the COVID-19pandemic, which is a tough test for art and cultural actors. Thecondition of the performers of arts and culture is not far from the twothings that must be canceled or postponed. However, the actors stillsurvive by holding virtual shows. Performers of arts and culture invitethe audience to donate to communities affected by the COVID-19pandemic through the holding of the virtual show. The unfavorableimpact of changing the virtual performing arts culture is changingthings that are abstract to concrete, and vice versa, namely fromconcrete to abstract. Making creative industry players of traditionalperforming arts, in this case the owners of capital, can easily savevarious costs of the production process. Another impact is that itmakes the appreciator, in this case humans, no longer able to interactwith fellow humans because they spend more of their timeappreciating the show virtually